2013
DOI: 10.1111/lam.12049
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of salt-alkaline effluent with industrial reactive dyes by laccase-producing basidiomycetes strains

Abstract: Significance and Impact of the Study: The identification of fungal strains and/or ligninolytic enzymes able to act in textile effluents is a topic of great interest for decolorization of Cibacron Brilliant Blue and Cibacron Red dyes present in a salt-alkaline synthetic textile effluent. The decolorization is improved by establishing the nitrogen source and amount to be used during the fungal action on the textile effluent. Laccase was the main enzyme involved on dyes decolorization by these fungal strains. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
2
13
0
3
Order By: Relevance
“…The activities presented in this study were already observed with other strains of P. sanguineus [9,26]. Laccase activity was observed using guaiacol as a substrate.…”
Section: Decolorization and Enzyme Activities On Liquid Mediasupporting
confidence: 58%
See 4 more Smart Citations
“…The activities presented in this study were already observed with other strains of P. sanguineus [9,26]. Laccase activity was observed using guaiacol as a substrate.…”
Section: Decolorization and Enzyme Activities On Liquid Mediasupporting
confidence: 58%
“…The results showed a significant decrease of decolorization with increasing dye concentration, as well as very important differences between the two dyes at the same concentrations ( Figure 1). In literature, the concentrations usually used are less than 0.2 g/L [4,9,[22][23][24]. In this study, a concentration of 0.3 g/L of RB4 was optimal with a decolorization rate of 98%.…”
Section: Effect Of Concentration and Temperature On Dyes Decolorizationmentioning
confidence: 78%
See 3 more Smart Citations